The roles of Member Relationship Proneness (MRP) and Programme Relationship Orientation (PRO) in creating store loyalty: evidence from retail loyalty programmes in Malaysia / Nor Asiah Omar, Rosidah Musa and Faridah Hassan - Omar, Nor Asiah; Musa, Rosidah; Hassan, Faridah (Faculty of Business and Management ; UiTM Press, 2007)
Investigations to determine whether member relationship proneness and programme relationship orientation could influence satisfaction, commitment and ultimately store loyalty are critical to elucidate the roles and significance of the constructs and advancing management practise. Accordingly, in line with this direction, our research aims to assess the effects of relationship proneness and relationship orientation offered by few leading retail storesin Malaysia on its members' loyalty towards the store. What is more, we also attempt to explore the roles of programme satisfaction and programme commitment in the hypothesised framework. The data set utilised in this study has been obtained via drop-off and collect technique, where a sample of 400 retail loyalty programmes' members was analysed. An integrative conceptual model was developed and tested using structural equation modelling analysis approach. The results exemplify thai member relationship proneness is a strong driver of programme satisfaction as well as programme commitment. Unexpectedly, programme satisfaction is not a significant predictor of store loyalty but, it has an indirect effect on store loyalty mediated by programme commitment. Our findings bring to light important implications for future research and management practice.